EFEKTIVITAS PEMBELAJARAN BERBASIS MASALAH, PEMBELAJARAN BERBASIS PROYEK LITERASI, DAN PEMBELAJARAN INKUIRI DALAM MENINGKATKAN KEMAMPUAN KONEKSI MATEMATIS - Abidin, Zaenal (Universitas Muhammadiyah Surakarta, 2020)
The aims of this research to explains the effectiveness of increasing students' mathematical connection abilities that obtain problem-based learning, project-based learning literacy and inquiry learning. The students' connection in the mathematics of elementary school was very low. It was because students have not been facilitated to develop mathematical connection skills correctly. This research was in the form of a quasi-experimental design of The Randomized Pretest-Posttest Control Group Design. Based on the results, Problem-based learning was the most effective model compared to other learning models in facilitating mathematical connection skills. It was because problem-based learning can present problems in the context of learning that requires high-level thinking. Thus training students to always connect mathematical concepts with daily context problems. Project-based learning literacy was very effective and better than inquiry in facilitating connection skills. It was because students create literacy works that connect mathematical concepts and daily context applications. However, students were less facilitated in practising mathematical concepts. Furthermore, inquiry learning was good enough in facilitating students' connection skills. However, students have not been allowed to use mathematical concepts in the context of everyday life. Students were only facilitated to find concepts, so students have not been facilitated to develop mathematical connection skills.